Glucose Production from Cellulosic Sludge Innovating Wastewater Recovery - Federico Micolucci; Nicola Frison (Chemical Engineering Transactions)
The transition from conventional wastewater treatment toward resource recovery and energy efficiency has become a central focus in wastewater treatment plant optimization. This study investigates the integration of pre-filtration and cellulosic primary sludge (CPS) hydrolysis as a strategy to enhance carbon recovery while reducing energy consumption. Using pilot-scale and batch experiments, the efficiency of CPS recovery via rotating belt filtration was compared with conventional pre-sedimentation, and hydrolysis conditions were optimized to maximize cellulose degradation and fermentable carbon production. The results demonstrated that mesophilic conditions (38°C) enabled up to 42% cellulose degradation of the CPS without pH adjustment, while alkaline hydrolysis (pH 12, at thermophilic 55°C) achieved the highest soluble chemical oxygen demand (sCOD) production. The observed correlation between total suspended solids reduction and sCOD increase confirms that CPS hydrolysis enhances the availability of bioavailable organics (e.g. Glucose, Xylose), which can serve for example as an internal carbon source for biological nutrient removal processes. Additionally, the hydrolysate’s potential for volatile fatty acid production highlights new opportunities for biopolymer synthesis and resource recovery. Energy balance calculations indicate that CPS removal before biological treatment could reduce aeration energy consumption by 5–15%, translating into annual savings of 149,480–442,776 kWh for a treatment plant of 150,000 people equivalent (PE). These findings support the role of CPS pre-filtration and hydrolysis in transforming wastewater treatment plants into energy-efficient water resource recovery facilities.